О постэмбриональном развитии клещей семейства Rhodacaridae Oudemans, 1902 - Щербак, Г.И. (Вестник зоологии, 1982)
Chaetological idiosome analysis in the mite family Rhodacaridae O u d e m a n s , 1902 during all developmental stages shows that I-VI tergites and I-V sternites are well pronounced on larval podosome, I X - X I tergites and sternites- on opistosome,VII and VIII tergites and VI andVII sternies appearin protonymph and VIII sternite - in deutonymph. Postembryonic Rhodacarid mites development is designated as a strictly limited anamorphosis with some elements of epimorphosis.